Crystal growth of HAp on plate-like ZnO particles using APTES as surface treatment agents. Issue 1 (2nd January 2023) - Amano, Masato; Shibata, Hirobumi; Hashimoto, Kazuaki
ABSTRACT: We successfully prepared Hydroxyapatite/Zinc oxide (HAp/ZnO) composite particles with hexagonal plate-like shapes. The surface of the ZnO particles was treated with (3-aminopropyl)triethoxysilane (APTES) as a scaffold for the crystallization of HAp from the precursor solution. From the results of XRD measurements and SEM images of composite particles, formation of HAp on the ZnO particles was revealed. In addition, diffraction peaks associated with the (0 0 2) and (0 0 4) planes of HAp were clearly observed. They also revealed that the HAp/ZnO composite particles had a c -face orientation. Furthermore, element mapping analysis by EPMA showed that the elemental distributions of Ca, P and Zn of the composites were almost coincident. These results suggested that the formation of HAp occurred on the ZnO particles. In contrast, the ZnO particles without APTES treatment readily dissolved in the precursor solution and the diffused Zn 2+ ions reacted with PO4 3- ions and Ca 2+ ions to form CaZn2 (PO4 )2 . APTES treatment of the ZnO surfaces appeared to prevent the dissolution of ZnO in the solution and induce the adsorption of anions such as phosphate on ZnO.